Venous Thromboembolism in a Young Man With Fused Renal Ectopia - Tomidokoro, Daiki (JACC Case Rep, 2020)
A 19-year-old man presented with chest pain after a trans-Pacific flight. Venous thromboembolism was diagnosed and treated with catheter-directed thrombolysis. Genetic testing revealed factor V Leiden mutation. In addition to the flight history and genetic hypercoagulability, a renal abnormality causing an external compression over the inferior vena cava was suspected to be a contributing factor. (Level of Difficulty: Intermediate.)